Transition regime between high-velocity and hypervelocity impact in metals – A review of the relevant phenomena for material modeling in ballistic impact studies. (September 2022) - Signetti, Stefano; Heine, Andreas
Highlights: We review modeling approaches for metals in terminal ballistics and address how they can be extended toward hypervelocity, with a focus on thermal effects. An extensive survey on HVIS, IBS and IJIE issues, technical reports, and other related impact research literature is performed. Materials phenomenology across different regimes in relation to simulation modeling is reviewed. A specific analysis on simulation works shows that modeling practices are consistent with the phenomenological characterization of the transition regime . Implications for future modeling research are derived. Abstract: In this work, we attempt to address the question how established modeling approaches for metals in terminal ballistics can be extended towards higher impact velocities that are still below the threshold of purely hydrodynamic behavior. While at the upper bound of the high-velocity penetration regime the effects of material strength and failure are dominating, the ideal hydrodynamic behavior is still not achieved until velocities of several kilometers per seconds. As shown by the authors in a precedent work, this transition regime lies between about 2 to 9 km/s –for the most common metal combinations in impact research– and it is of paramount interest since characterized by the coexistence of different multi-physics phenomena with a gradual transition from effects dominated by strength to those connected with the increase of internal energy, such as thermal softening and melting. In order to assess the implications for material modeling at velocities moderately above the regime of terminal ballistics, here we perform an extensive review of related literature with a focus on the relevant phenomena for impact modeling of metals at velocities lying in the transition regime.